Silencing of circ_0078607 prevents development of gastric cancer and inactivates the ERK1/2/AKT pathway through the miR-188-3p/RAP1B axis. Issue 9 (23rd April 2021) - Bian, Weixin; Liu, Zhiqiang; Chu, Yanjie; Xing, Xiaofang
Abstract : The aim of this study is to explore the expression and mechanism of circ_0078607 on proliferation and apoptosis of gastric cancer. Real time PCR (RT-PCR) was performed to detect the expression of circ_0078607 in gastric cancer tumor tissues, plasma and cell lines. Cell viability was detected by cell counting Kit-8. Cell proliferation ability was assessed by cell cycle assay. The samples were analyzed by flow cytometry for the detection of apoptosis. Luciferase assay and RNA immunoprecipitation (RIP) were carried out to verify the relationship between circ_0078607 and miR-188-3p, miR-188-3p, and RAP1B. Western blot was employed to detect the protein level of RAP1B, ERK1/2 and AKT. In vivo, the effect of circ_0078607 on gastric cancer tumor growth was detected by lentivirus vector injection. Here, we found the increased level of circ_0078607 in gastric cancer tissues, gastric cancer patients plasma and cell lines. Knockdown of circ_0078607 could prevent proliferation and induce cell apoptosis in MKN-28 cells. Then we verified that circ_0078607 could interact with miR-188-3p by performed luciferase assay and RIP. Furthermore, we observed that RAP1B was a potential target of miR-188-3p. Next, we found that miR-188-3p inhibitor or overexpression of RAP1B could prevent the anti-tumor function of sh-circ_0078607. Silencing of circ_0078607 inhibited ERK1/2/AKT signal pathways via regulating miR-188-3p/RAP1B. In vivo, knockdown of circ_0078607 inhibited tumor growth. Knockdown of circ_0078607 inhibits the proliferation and induces apoptosis of gastric cancer via miR-188-3p/RAP1B signal pathway.